2002
DOI: 10.1016/s0006-3495(02)75282-x
|View full text |Cite
|
Sign up to set email alerts
|

Thin Filament Regulation and Ionic Interactions between the N-terminal Region in Actin and Troponin

Abstract: The N-terminal region in actin has been shown to interact with both myosin and troponin (Tn) during the cross-bridge cycle and in regulation. To study the role of this region in regulation, we used yeast actin mutants with increased and decreased numbers of acidic residues. The mutants included D24A/D25A, with Asp(24) and Asp(25) replaced with alanines; DNEQ, with the substitution of Asp(2) and Glu(4) with their amide analogs; and 4Ac, with Glu(3) and Asp(4) inserted in lieu of Ser(3). In the in vitro motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Therefore the biochemical effects of these polyphenols are of great interest as they could potentially lead to prevention or new treatments of heart disease. [8], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the biochemical effects of these polyphenols are of great interest as they could potentially lead to prevention or new treatments of heart disease. [8], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several observations support this model. First, phylogenetic clustering of the actin sequences examined demonstrated that the animal cytoplasmic actins and two of the protist actin sequences (i.e., Mb-ACT and Ac-ACT1), which suppressed loss of plant actin function, are quite distinct in their sequences from the plant actins ( Figure 1B role has been shown for the N-terminal region containing several acidic amino acids (Lasa et al, 1997;Hinz et al, 2002;Wong et al, 2002;Lu et al, 2005). Therefore, we were surprised to observe that the animal cytoplasmic actins (i.e., Hs-ACTG1, Hs-ACTB, and Ci-ACTB1) and the protist actins (i.e., Ac-ACT1 and Mb-ACT), which are two amino acids shorter than all plant actins at the N terminus (see Supplemental Figure 2 online), efficiently substituted for plant actins.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast actin, only 1 cysteine (Cys-374) is readily modified by chemical means. Therefore, substituting Cys-374 with another amino acid results in a Cys-light version of actin that can be used to introduce cysteine residues at other locations throughout the actin structure, as performed in various previous studies (Feng et al 1997;Kim et al 2000;Orlova et al 2004;Shvetsov et al 2002;Wong et al 2002). These studies showed that the substitution of Cys-374 had no significant effect on the properties of actin.…”
Section: A Cysteine Engineering Strategy For Producing Yeast Nonpolymmentioning
confidence: 93%